Saudi Efl Undergraduate Students’ Responses To Cognitive Stress And Metacognitive Reading Strategies In Reading Comprehension - Ahmad Abu Khait, Rema Oqla (2022)
This study examined Saudi EFL students’ responses to cognitive stress and the use of metacognitive reading strategies in reading comprehension. It is recognised that learning in any form depends on cognitive, social, and emotional factors which are interrelated. Reading comprehension in EFL (English as a Foreign Language) can be both tiring and stressful and, to be successful, EFL learners must have practical and coping strategies that they can apply with confidence and competence in comprehension of reading texts. The study also examined the effects of metacognitive strategies awareness, demographic factors, and cognitive load on Saudi EFL undergraduate students’ reading performance. Cognitive stress is conceptualized in this study as the stress created by manipulation of time-on-task and text difficulty.